Ketogenic Diet-Induced Diabetic Ketoacidosis in a Young Adult with Unrecognized Type 1 Diabetes - Suranut Charoensri; Jin Sothornwit; Akeatit Trirattanapikul; Chatlert Pongchaiyakul (Case Reports in Endocrinology)
Ketogenic diet, a very low-carbohydrate diet and high-fat diet, has emerged as a popular approach for weight reduction, particularly in young adults. However, a serious but rare complication of the ketogenic diet is ketoacidosis associated with low carbohydrate intake, which should be cautiously monitored in people with a predisposition to the condition. We report a 22-year-old Thai woman with an unremarkable past medical history who presented with an acute onset of dyspnea of 2 days’ duration. Diabetic ketoacidosis was diagnosed by elevated capillary blood glucose, significant metabolic acidosis, and a high serum beta-hydroxybutyrate level. Low C-peptide level and positive islet autoantibodies confirmed the new diagnosis of type 1 diabetes in this patient. After her conditions were stabilized, the patient revealed that she began a ketogenic diet for weight reduction 4 days before her illness. Other precipitating factors were not identified. This highlights that ketogenic diet may increase diabetic ketoacidosis risk at the presentation of previously unrecognized type 1 diabetes.